FITOSSOCIOLOGIA DA VEGETAÇÃO ARBÓREA DA RESERVA FLORESTAL DO SACAVÉM, SÃO LUÍS, MARANHÃO (BRASIL) - Muniz, Francisca Helena; Cesar, Oswaldo [UNESP]; Monteiro, Reinaldo [UNESP] (Instituto Nacional de Pesquisas da Amazônia, 1994)
A phytosociological study was carried out in 0.5 ha of remaining patches of 'Pre-Ama-zonian' humid tropical forest within the Sacavém Forest Reserve, located in the municipality of São Luís, state of Maranhão, Brazil (2° 32'S; 44° 17'W). The total area comprised of fifty 10x10 m quadrats in which 410 trees with a minimum perimeter at breast height (PBH) of 15 cm were sampled, including 5 dead individuals. There were found 110 species of 66 genera in 34 families. The DBH varied between 4.8 cm and 86.7 cm, with an average of 16.28 cm. The minimum, mean and maximum heights were 2.0 m, 11.16m and 25.0 m, respectively. The total basal area was 14.207 m2 or 28.4140 rrrVha with an average of 0,07 m2/tree; the absolute density was 820 trees/ha. The five most importante families in IVI were Leguminosae, Chrysobalanaceae, Meliaceae, Myrtaceae and Arecaceae, making up 49.24% of the total. The five most important species in IVI were Licaniacf. incana Aubl., Guaina guidonia (L.) Sleumer, Copaifera langsdorffiiDesf., Dipteryx lacuniferaDucke and one morpho-species (Unknown 1 ). As much as 60% of the species had only one or two individuals. The Shannon & Weaver diversity index (Η') was 4.189. Although the area studied is comparatively small, several comparisons made with surveys for other Amazonian forest locations led to the conclusion that the Sacavém Reserve has similar richness, density and dominance.

Foi amostrada fitossociologicamente uma área de 0,5 ha de mata na Reserva Florestal do Sacavém, distando cerca de 7 Km do centro da cidade de São Luís (232'S; 4417'W), em manchas remanescentes de floresta tropical úmida, denominada localmente de Pré-Amazônia. A área foi dividida em 50 parcelas de l0x 10 m ( 100 m2), nas quais foram amostrados 410 indivíduos com PAP a partir de 15 cm, pertencentes a 34 famílias, 66 gêneros e 110 espécies, além de 5 indivíduos mortos não considerado na análise fitossociológica. O DAP variou de 4,8 cm a 86,7 cm, ficando a média cm 16,28 cm. As alturas mínima, média e máxima foram, respectivamente, 2,0 m, 11,16 m e 25,0 m. A área basal total foi de 14,207 m2, equivalente a 28,4140 m2/ha, com média de 0,07 m2/indivíduo, e a densidade absoluta foi de 820 indivíduos/ha. As cinco famílias mais importantes em IVI foram Leguminosae, Chrysobalanaceae, Meliaceae, Myrtaceae e Arecaceae, perfazendo 49,24% do total. As primeiras cinco espécies em IVI foram Licania cf incana Aubl., Guarea guidonia (L.) Sleumer, Copaifera langsdorffii Desf., Dipteryx laamiferaDucke c uma morfo-espécie (Desconhecida 1). Cerca de 60% das espécies consideradas apresentaram apenas 1 ou 2 indivíduos. O índice de diversidade de Shannon e Weaver (Η') foi de 4,189. Foram feitas comparações com diversos trabalhos realizados em florestas amazônicas, confirmando que a área em estudo é comparável àquelas em riqueza, densidade e dominância, embora a área tenha sido subdimensionada.
Phytosociology of a woody vegetation in the Sacavém Forest Reserve - São Luis. State of Maranhão(Brazil)
Keywords: Phytosociology; 'Pre-Amazonian' forest; Sacavém Forest Reserve (São Luís, Maranhão); Fitossociologia; Floresta Pré-Amazônica; Reserva Florestal do Sacavém (São Luís-MA)